Development Strategy of Sharia Insurance in Indonesia - Aslam Mei Nur Widigdo; Aam Slamet Rusdiyana (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The background of the research is the low market share of Indonesia's sharia insurance compared to its potential and the decline in assets of the Indonesian sharia insurance industry in 2020 and 2021 compared to 2019. The purpose of the study is to analyze the problems faced by the sharia insurance industry and formulate strategies that can be used in dealing with these problems in order to increase market share. This study uses a qualitative paradigm approach with ANP (Analytical Network Process) as an analytical tool. The type of data is primary data obtained through in-depth interviews and filling out questionnaires by sharia insurance experts from industry practitioners, associations, academics and regulators. Software Super Decision 2.10 is used as a data measurement and analysis tool. The result of research shows that the problems faced by the sharia insurance industry in Indonesia can be grouped into four aspects, namely human resources, infrastructure, products, and markets.  The study also found that the right strategy related to the development of the sharia insurance market in Indonesia is to combine four strategies that have been formulated with sequential priorities starting from institutional strengthening, resources strengthening, product development and marketing improvement.